105 Paediatric sudden sensorineural hearing loss: pooled analysis and systematic review. (22nd November 2019) - Reading, Jacob; Hall, Andrew; Nash, Robert
Abstract : Purpose: Sudden sensorineural hearing loss (SSNHL) is defined as hearing loss in one or both ears of ≥ 30 dB, developing within 3 days, affecting at least 3 contiguous frequencies. It is rare in children, but if untreated can cause significant morbidity. Hearing loss during critical periods of development may cause life-long social, behavioural and mental sequelae. However, little is known about its aetiology, management and prognosis. Methods: A systematic literature review of paediatric SSNHL on PubMed, Embase, and the Cochrane CENTRAL database was performed on 31st June 2019 according to the PRISMA recommendations. 620 papers met appropriate MESH criteria, of which 14 met inclusion criteria for further analysis. 13 of these were level 4 evidence (retrospective records reviews) and 1 was level 2b evidence (prospective cohort study). A pooled patient population of 754 individuals was analysed. Results: Most cases of SSNHL in children were idiopathic in aetiology. Other reported aetiologies included viral infection, trauma, ototoxic drugs and structural abnormalities. Systemic steroids were the mainstay of treatment in all included studies. Recovery was defined as any improvement in hearing following the initial episode of hearing loss, from 'slight' to 'complete' recovery. Recovery ranged from 20% to 100% in the included studies, with a pooled rate of 47%. Only one study reported a recovery rate without treatment, of 6.25%. Conclusion: Paediatric SSNHL is an important condition of which little is known. Even with current best practice, fewer than half of children with SSNHL will recover their hearing.